SPE Improved Oil Recovery Symposium 2012
DOI: 10.2118/154236-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Waterflood at Reduced Capillarity

Abstract: The thesis includes research on the hybrid EOR process of low salinity surfactant injection. The main objective was to investigate whether combining the two processes of low salinity injection with surfactant injection would be more efficient than either of the processes alone. I big thank you to all fellow students and colleagues at CIPR that I have met over the years, many of which I still consider as close friends. A big thank you goes to a very special person, Bartek Vik, for his support and motivation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 69 publications
2
42
0
Order By: Relevance
“…The results showed that significantly more oil was mobilised by the hybrid process (IFT reduction and low salinity) compared to what is expected from a sole reduction in IFT (increase in capillary number) due to the added surfactant. This has later been confirmed by Spildo et al (2012) and Johannessen and Spildo (2013).…”
Section: Low Salinity Surfactant Injectionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results showed that significantly more oil was mobilised by the hybrid process (IFT reduction and low salinity) compared to what is expected from a sole reduction in IFT (increase in capillary number) due to the added surfactant. This has later been confirmed by Spildo et al (2012) and Johannessen and Spildo (2013).…”
Section: Low Salinity Surfactant Injectionsupporting
confidence: 52%
“…The studies have shown a moderate increase in oil recovery during injection of low salinity brine (0.2-0.5 wt% NaCl). Some, but not all, of these experiments have included observations indicating fines migration (see for example Alagic and Skauge, 2010;Gamage and Thyne, 2011;Alagic et al, 2011;Spildo et al, 2012). The factors controlling whether or not fines migration and possible formation damage occurs are not fully understood.…”
Section: Effect Of Salinity On Clay Stability and Surfactant Retentionmentioning
confidence: 99%
“…to be an economical process 4) . Nowadays because of environmental fates, natural based surfactants can be used instead of industrial surfactants and many researchers have studied on these kinds of surfactants in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the degree of oil recovery improvement relies on multicomponent ion exchange, clay contents, formation water composition, oil composition and initial water saturation. A few mechanisms have been proposed to explain the positive effect, including: migration of fines (Tang and Morrow, 1999), interfacial tension reduction (McGuire and Chatham, 2005), multicomponent ionic exchange (Lager et al, 2008), PH driven wettability change (Lager et al, 2008;McGuire and Chatham, 2005), double-layer expansion (Ligthelm et al, 2009), desorption of organic material from clay surface (Austad et al, 2010), wettability alternation (Yousef et al, 2012), mineral dissolution (Aksulu et al, 2012), and microscopically diverted flow (Skauge 2008;Spildo et al 2012). These mechanisms lead to modification of rock wettability from oil-wet or intermediate/water wet; therefore, residual oil saturation is reduced, and ultimate oil recovery is improved.…”
Section: Introductionmentioning
confidence: 99%